Songbirds : a novel - Lefteri, Christy, 1980- (Ballantine Books, 2021)
"From the prize-winning author of The Beekeeper of Aleppo, a stunning novel about the disappearance of a Sri Lankan nanny and how the most vulnerable people find their voices. "It began with a crunch of leaves and earth. So early, so cold, the branches shone with ice. I'd returned to collect the songbirds. They are worth more than their weight in gold." Yiannis is a poacher, trapping the tiny protected songbirds that stop in Cyprus as they migrate each year from Africa to Europe and selling them on the black market. He dreams of finding a new way of life, and of marrying Nisha, who works on the island as a nanny and maid--having left her native Sri Lanka to try to earn enough to support her daughter, left behind and raised by relatives. But Nisha has vanished; one evening, she steps out on a mysterious errand and doesn't return. The police write off her disappearance as just another runaway domestic worker, so her employer, Petra, undertakes the investigation. Petra's unravelling of Nisha's last days in Cyprus lead her to Nisha's friends--other maids in the neighborhood--and to the darker side of a migrant's life, where impossible choices leave them vulnerable, captive, and worse. Based on the real-life disappearance of domestic workers in Cyprus, Christy Lefteri has crafted a poignant, deeply empathetic narrative of the human stories behind the headlines. With infinite tenderness and skill, Songbirds offers a triumphant story of the fight for truth and justice, and of women reclaiming their lost voices"--